2019
DOI: 10.1021/acs.inorgchem.9b00515
|View full text |Cite
|
Sign up to set email alerts
|

Trigonal to Pentagonal Bipyramidal Coordination Switching in a Co(II) Single-Ion Magnet

Abstract: In molecular magnetism and single-ion magnets in particular, the observation of slow relaxation of the magnetization is intimately linked to the coordination environment of the metal center. Such systems typically have blocking temperatures well below that of liquid nitrogen, and therefore detailed magnetic characterization is usually carried out at very low temperatures. Despite this, there has been little advantage taken of ultralow temperature single-crystal X-ray diffraction techniques that could provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The parameter α for 2 is within the limit of 0.43–0.63, which envelopes those observed for Co II -based SMMs and suggests a narrow-to-moderate distribution of magnetic relaxation. After that, we analyzed the temperature-dependent relaxation time by the Arrhenius law (τ = τ 0 ·exp( U eff / k B T )); the energy barrier and relaxation time were U eff = 20.4 K and τ 1 = 9.1 × 10 –8 s under 0 Oe DC field (Figure d). Compared with other Co-SMMs, the SMM behavior of nanocluster 2 is weaker than that of most Co-SIMs. But for high nuclear cobalt clusters, nanocluster 2 has a more obvious slow relaxation behavior, which is of great significance for the study of high nuclear Co-SMMs.…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…The parameter α for 2 is within the limit of 0.43–0.63, which envelopes those observed for Co II -based SMMs and suggests a narrow-to-moderate distribution of magnetic relaxation. After that, we analyzed the temperature-dependent relaxation time by the Arrhenius law (τ = τ 0 ·exp( U eff / k B T )); the energy barrier and relaxation time were U eff = 20.4 K and τ 1 = 9.1 × 10 –8 s under 0 Oe DC field (Figure d). Compared with other Co-SMMs, the SMM behavior of nanocluster 2 is weaker than that of most Co-SIMs. But for high nuclear cobalt clusters, nanocluster 2 has a more obvious slow relaxation behavior, which is of great significance for the study of high nuclear Co-SMMs.…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…In another study, a penta-coordinated Fe­(III) complex was reported by Mossin et al with the intermediate ground-spin state that exhibits slow magnetic relaxation along with the axial zero field splitting (ZFS) with D = −11 cm –1 . In addition to these complexes, there are several other reports in the literature that make it evident that penta-coordinated TBP complexes induce high magnetic anisotropy and are promising candidates for the application of magnetic properties. Continuous effort has been made for the meticulous understanding of the factors that affect the magnetic anisotropy in TBP complexes related to ligand-field and magnetostructural correlations. , …”
Section: Introductionmentioning
confidence: 99%
“…Their potential applications in magneto‐memory devices, spintronics and molecular switches have become more and more appealing [3–8] . The magnetic properties of switchable molecular materials, such as spin transition, valence tautomerism, etc., strongly couple to external perturbations and display a variety of controllable stimulus‐response behaviors triggered by heat, light, or pressure [9–24] . More importantly, accompanied by the switch of magnetic properties, the explicit structural changes of the molecule draw extensive attention thanks to its beneficial insights into the magneto‐structural correlations hidden in phase transition and further shed light on the design tactics [25–34] …”
Section: Introductionmentioning
confidence: 99%